Inflation-Adjusted Medicare Reimbursement for Hip Arthroscopy Fell by 21.1% on Average Between 2011 and 2022 - Allison Y. Kufta, B.S; David R. Maldonado, M.D; Cammille C. Go, B.S; Andrew J. Curley, M.D; Paulo Padilla, M.D; Benjamin G. Domb, M.D (Elsevier, 2023)
Purpose: To examine Medicare reimbursement for hip arthroscopy from 2011 to 2022. Methods: The seven most common procedures performed with hip arthroscopy by a single surgeon were gathered. The Physician Fee Schedule Look-Up Tool was utilized to access financial data of the associated Current Procedural Terminology (CPT) codes. The reimbursement data for each CPT were gathered from the Physician Fee Schedule Look-Up Tool. With the consumer price index database and inflation calculator, reimbursement values were adjusted for inflation to 2022 U.S. dollars. Results: Following an adjustment for inflation, it was found that reimbursement rate for hip arthroscopy procedures on average was 21.1% lower between 2011 and 2022. The average reimbursement per CPT code for the included codes was $899.21 in 2022 compared to inflation adjusted $1,141.45 in 2011, a difference of $242.24. Conclusions: From 2011 to 2022, the average inflation-adjusted Medicare reimbursement has steadily declined for the most common hip arthroscopy procedures. As Medicare is one of the largest insurance payers, these results have substantial financial and clinical implications for orthopaedic surgeons, policy makers, and patients. Level of Evidence: Level IV, economic analysis.